Determination The Cooling Capacity of The Fan Coil Unit (FCU) in A Hotel Room - Based on Heat Transfer Analysis - Luh Putu Ike Midiani; I Wayan Adi Subagia; I Made Angga Antara (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
Fan Coil Unit (FCU) with the appropriate cooling capacity is needed to obtain room thermal comfort. FCU installed based on the cooling load of the room. Cooling load is affected by room volume, material of : wall, floor, roof, equipment in a room, ventilation, infiltration, windows, outdoor air temperature and humidity, indoor air temperature and  humidity. Appropriate and correct FCU installation will have an impact on the energy use of a building. Energy saving efforts are made when determining FCU capacity by calculating cooling load by analyzing heat transfer. This paper investigates and analyzes the amount of room cooling load using the CoolPack application. Calculation of cooling capacity using the CoolPack application is carried out after determining the thermal conductivity and material thickness, thermal resistance of the inner surface and outer surface of the wall, roof, floor, and heat transfer coefficient. Based on the results of calculations and analysis, it was concluded that the total cooling load was 3.58 kW. Furthermore, the FCU capacity to be installed must match the FCU capacity available on the market and be greater than the total cooling load in order to achieve the expected comfort. Proper and correct installation of FCUs will have an impact on energy use in a building is an effort to implement energy saving.